Three-dimensional CoOOH nanoframes confining high-density Mo single atoms for large-current-density oxygen evolution - Tang, Lei; Yu, Liang; Ma, Chao; Song, Yao; Tu, Yunchuan; Zhang, Yunlong; Bo, Xin; Deng, Dehui (Journal of materials chemistry. A, Materials for energy and sustainability, 2022)
Layered transition-metal oxyhydroxides (MOOHs) emerge as promising noble-metal-free electrocatalysts for the oxygen evolution reaction (OER), yet are subject to a limited number of active sites at edges with an inactive basal plane. Herein, we report that a large number of in-plane active sites can be generated by confining high density of 16 wt% molybdenum single atoms in the basal-plane lattice of CoOOH (Mo-CoOOH). By constructing robust three-dimensional (3D) nanoframes to prevent layer-stacking and maximize exposure of active basal planes, the catalyst achieves an unprecedented OER activity at a large current density of 2000 mA cm −2 , exhibiting the lowest overpotential of 400 mV among all previously reported catalysts with a high durability of over 120 hours. Multiple spectrometry characterization studies and first-principles calculations reveal that lattice-confined Mo atoms can bond moderately with OER intermediates, thereby serving as active sites for the reaction. This strategy provides a new path to design high-performance MOOH electrocatalysts with rich in-plane active sites. This work reports that via confining high density of 16 wt% single Mo atoms into the lattice of CoOOH nanosheets and simultaneously fabricating robust nanoframes of the nanosheets, an unprecedented large-current-density OER activity is achieved.